Próg rentowności jako narzędzie budżetowania - Szczęsny, Wiesław (Break-even Point as an Instrument of the Financial Management, 2006)
The break-even analysis belongs to the elementary instruments of the financial management. It supports the decision process of enterprises because it permits to define the relationship between the sales value and the profitability. The article presents the attempt to modify this instrument taking some values of classic formula known from financial bibliography into consideration. In the suggesting model the growth of sales value is the independent factor and it is possible to estimate the return on sales (ROS) on the basis of it. Two of its variants are presented in the article, depending on the own manufacturing abilities or extra enterprise's investment expenditures. The author gives his view that the break-even as the elementary instrument of the financial management is the essential element in the budgeting process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 618-622